Effects of an active hand exoskeleton on forearm muscle activity in industrial assembly grips. - Mayer, Tobias A.; Harsch, Ann-Kathrin; Koska, Daniel; Hensel-Unger, Ralph; Maiwald, Christian; Brandl, Christopher; Nitsch, Verena (Work, 2022)
BACKGROUND: The Bioservo Ironhand® is a commercially available active hand exoskeleton for reducing grip-induced stress. OBJECTIVES: The study aimed at quantifying the effect of the Ironhand® exoskeleton on the myoelectric muscle activity of forearm flexor and extensor muscles in three relevant assembly grip tasks: 2-Finger-grip (2Finger), 5-Finger-grip (5Finger) and Full grip (FullGrip). METHODS: Twenty-two subjects were tested in three different exoskeleton conditions for each grip task (overall 3×3×10 = 90 repetitions in randomized order): Exoskeleton off (Off), Exoskeleton on, "locking tendency" 0% (On_LT0), and Exoskeleton on, "locking tendency" 85% (On_LT85). Muscle activity was measured at 25% of the participant's maximum grip force using two EMG sensors at the M. flexor digitorum superficialis (M.FDS) and one at the M. extensor digitorum (M.ED). RESULTS: The effect of the Ironhand® exoskeleton varied depending on the grip task and the participant's sex. A statistically significant reduction in muscle activity of the M.FDS was found only for male subjects in the FullGrip condition. No reduction of muscular activity in the M.FDS was found for the other grip tasks (2Finger, 5Finger). For the females in the 2Finger condition, mean muscle activity of M.FDS even increased significantly in On_LT0 compared to Off. Besides differences between grip tasks and sex, the current study revealed substantial individual differences. CONCLUSIONS: In addition to testing for statistical significance, a detailed exploratory analysis of exoskeleton effects at subject level should be performed to evaluate these from a safety and regulatory perspective.